Changes in product design and development processes: design thinking, service design and user experience - Del Giorgio Solfa, Federico (2021)
This article addresses the new theories and concepts of design management: design thinking, user experience (UX) and service design. They consider people's experiences and focus on the characteristics of each one of them. From industrial design, the scope and relationships between these definitions-now better visible-were analyzed, which always belonged to the design field of the discipline, from which an attempt was made to identify how they influence innovation, design and development of new products. To account for the evolution that the design field has had, the most significant processes are contrasted to visualize the differences that make this change fundamental. Finally, it is concluded on its strategic relevance for the application in public and private organizations. Also taking into account how these theories are methodologically incorporated into the set of activities inherent to industrial design. Keywords: industrial design, design process, user experience, design thinking, service design, human-centered design.